2022
DOI: 10.1029/2021gl097602
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Mixed Clathrate‐Ice Shells on Ocean Worlds

Abstract: The habitability of oceans within icy worlds depends on material and heat transport through their outer ice shells. Previous work shows a methane clathrate layer at the upper surface of the ice shell of Titan thickens the convecting region, while on Pluto a clathrate layer at the base of the ice shell hinders convection. In this way, the dynamics of clathrate‐ice shells may be essential to the thermal evolution and habitability of ocean worlds. However, studies to date have not addressed the dynamics that dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
(206 reference statements)
0
9
0
Order By: Relevance
“…Both Ganymede and Titan have slightly higher gravities than Europa, which will increase the relative negative buoyancy of melt in ice and thus the rate of foundering. Titan is distinct amongst ocean worlds in our Solar System as it has liquid hydrocarbons at the surface and methane clathrates that are potentially entrained in the ice shell (Carnahan et al., 2022; Kalousová & Sotin, 2020; Tobie et al., 2005). Europa and other Galilean satellites also have oxidants present at the surface and potentially impurities within the ice shell (Buffo et al., 2020; Hand et al., 2006; Trumbo et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Both Ganymede and Titan have slightly higher gravities than Europa, which will increase the relative negative buoyancy of melt in ice and thus the rate of foundering. Titan is distinct amongst ocean worlds in our Solar System as it has liquid hydrocarbons at the surface and methane clathrates that are potentially entrained in the ice shell (Carnahan et al., 2022; Kalousová & Sotin, 2020; Tobie et al., 2005). Europa and other Galilean satellites also have oxidants present at the surface and potentially impurities within the ice shell (Buffo et al., 2020; Hand et al., 2006; Trumbo et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Kamata et al (2019) argue that a thin shell (∼10 km) of methane clathrates located at the base of the ice shell and atop the ocean could sustain a large temperature differential between the ocean and water-ice shell, preventing convection and lateral flow of the ice shell. Other studies identify a similar insulating effect for Ceres (Castillo-Rogez et al 2019) and Titan (Kalousová & Sotin 2020;Carnahan et al 2022). On Pluto, without clathrate's insulating effect and the inhibition of lateral ice flow, the ocean-uplift mass anomaly beneath Sputnik Planitia would Original content from this work may be used under the terms of the Creative Commons Attribution 4.0 licence.…”
Section: Introductionmentioning
confidence: 54%
“…have waned away by today (e.g., Kamata et al 2019;Carnahan et al 2022). However, whether Pluto's accretional composition and interior evolution support the formation and maintenance of an insulating methane clathrate layer has yet to be modeled.…”
Section: Introductionmentioning
confidence: 99%
“…Methane clathrates are not expected either because there is little methane in the system. Kamata et al (2019) and Carnahan et al (2022) have suggested methane clathrates to be abundant in large icy bodies due to the breakdown of abundant OM mixed with rock in the core of these bodies. In the case of Ceres, a relevant analog to the Uranian moons in terms of size (central pressure ∼150 MPa), radioisotope heat budget, and composition, Melwani shows that the output of methane from thermal metamorphism of the core is negligible (<10 −4 mol/kg).…”
Section: Appendix C: Conditions For Clathrate Formationmentioning
confidence: 99%